2023
DOI: 10.17221/373/2022-pse
|View full text |Cite
|
Sign up to set email alerts
|

The effect of deep-tillage depths on crop yield: A global meta-analysis

Abstract: Global soil compaction is occurring at an unprecedented rate (Eswaran 2004). Worldwide compaction has degraded an estimated 427 000 km 2 of soil (Sonderegger and Pfister 2021), particularly because of the development of heavy-agricultural machinery and intensification of the cropping system (Stoessel et al. 2018). As one of the main soil degradation types in the world, soil compaction causes high bulk density, poor aeration, low water conductivity, strong strength, and consequently reduces crop growth and yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…However, there have been a number of studies on different types of deep tillage. Huang et al [18] carried out a meta-analysis based on over 200 studies conducted worldwide, which showed that crop yield increases with deep tillage at 25-35 cm depth and then decreases with increasing tillage depth. According to the authors [18], the optimal depth of tillage for wheat, maize and soybean worldwide is 35 cm; and this depends on different climatic regions.…”
Section: The Effect Of Variable Depth Tillagementioning
confidence: 99%
See 2 more Smart Citations
“…However, there have been a number of studies on different types of deep tillage. Huang et al [18] carried out a meta-analysis based on over 200 studies conducted worldwide, which showed that crop yield increases with deep tillage at 25-35 cm depth and then decreases with increasing tillage depth. According to the authors [18], the optimal depth of tillage for wheat, maize and soybean worldwide is 35 cm; and this depends on different climatic regions.…”
Section: The Effect Of Variable Depth Tillagementioning
confidence: 99%
“…The analysis showed that a depth of 30 cm was more suitable for temperate zones such as the western United States, northern Europe, southern Russia and eastern China, which could increase crop yields. In general, 35 cm was suitable for most tropical regions and parts of temperate zones such as North and South America, Europe, Africa, South Asia, and southern Australia [18].…”
Section: The Effect Of Variable Depth Tillagementioning
confidence: 99%
See 1 more Smart Citation